2020
DOI: 10.1101/2020.01.16.908731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relating the past with the present: Information integration and segregation during ongoing narrative processing

Abstract: Real-life events unfold continuously over multiple minutes. In this study, in order to examine how the brain continuously integrates information while segregating the accumulated information from irrelevant inputs, a professional writer actively designed a narrative. Two unrelated storylines were interleaved across 30 one-minute segments (ABAB) and merged in a last (C) part, where narrative motifs unique to the A or B storylines recurred to induce reinstatement. Our fMRI results showed neural reinstatement of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Functional neuroimaging studies have used naturalistic, narrative stimuli to examine how we perceive 11,12 and remember 13 structured events based on memory of contexts, [14][15][16] prior knowledge or beliefs, [17][18][19] and emotional and social reasoning. [20][21][22] However, strikingly few neuroimaging studies have directly probed attention during naturalistic paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Functional neuroimaging studies have used naturalistic, narrative stimuli to examine how we perceive 11,12 and remember 13 structured events based on memory of contexts, [14][15][16] prior knowledge or beliefs, [17][18][19] and emotional and social reasoning. [20][21][22] However, strikingly few neuroimaging studies have directly probed attention during naturalistic paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, an fMRI study found evidence of integrated neural representations in a period shortly after encountering "bridge" events that linked previously unrelated experiences (Milivojevic et al, 2015). Behavioral signatures of a similar form of integration have been linked to neural reinstatement of relevant memories during the bridge learning experiences themselves (Chang et al, 2020). It thus appears that inferences dependent upon the integration of previously separate memories can stem from rapid changes in neural representations that occur largely online (during learning or immediately after).…”
Section: Discussionmentioning
confidence: 93%
“…Some forms of generalization, including the integration of information across otherwise separate memories can occur online during a learning experience (Chang et al, 2020;Milivojevic et al, 2015). The brain states that fluctuate with circadian rhythms, the physiological changes that cycle across the day, may influence this in-the-moment generalization.…”
Section: Introductionmentioning
confidence: 99%
“…The stronger hippocampal-PMC connectivity during higher centrality events might reflect greater reinstatement of other event representations cued by overlapping components (e.g., ref. 39 ).…”
Section: Narrative Network Centrality Modulates Hippocampal Encoding Signals During Movie Watchingmentioning
confidence: 99%